Health economic evaluations of perinatal complications with conflicting maternal-fetal interests: a scoping review protocol - Lihong Mo; Alfredo Lopez Aguirre; Nithya Sivakumar; Sakunrat Prompalit; Herman L. Hedriana; Jeffrey S. Hoch (BMJ Open, 2025)
Introduction Perinatal complications involving conflicts between maternal and fetal health interests present a unique challenge to health economic evaluations. No comprehensive synthesis exists of how such studies account for dual-patient outcomes. We aim to develop a scoping review protocol to map and critically examine the methodologies in this understudied area.Methods and analysis The scoping review will be conducted under the Joanna Briggs Institute (JBI) framework. It will include health economic studies, such as cost-effectiveness, cost utility and decision analysis studies, focusing on clinical conditions during pregnancy where maternal and fetal interests conflict. Cost analysis without effectiveness assessment will be excluded. Using comprehensive search strategies in Medline (Ovid), EMBASE (Elsevier) and Cochrane Library (Wiley), two independent reviewers will screen and identify relevant studies via abstract and full-text review. We will perform data extraction following an adapted form from the Consolidated Health Economic Evaluation Reporting Standards checklist, which includes the content details, such as the type of study, population, intervention, comparator, probability, utility, duration, cost, model types and uncertainty measurements. As we try to explore the impact of the health economic studies in clinical practice, we will include citation metrics of each study and whether the study was cited by practice guidelines and clinical trials in the data extraction. We will also apply the JBI Checklist for Economic Evaluations to assess the reporting completeness in each article. Results will be tabulated by clinical theme and synthesised narratively to highlight patterns in valuation approaches, gaps in current methods and impact on clinical guidelines.Ethics and dissemination This study does not require ethical approval as it involves secondary analysis of published data. Findings will be disseminated through peer-reviewed publications, conference presentations and stakeholder engagement activities.PROSPERO registration number CRD42024557324